Diagnostic value of a combination of next-generation sequencing, chorioretinal imaging and metabolic analysis: lessons from a consanguineous Chinese family with gyrate atrophy of the choroid and retina stemming from a novel OAT variant. Issue 3 (26th October 2018) - Huang, Junting; Fu, Jiewen; Fu, Shangyi; Yang, Lisha; Nie, Kailai; Duan, Chengxia; Cheng, Jingliang; Li, Yumei; Lv, Hongbin; Chen, Rui; Liu, Longqian; Fu, Junjiang
Abstract : Background/Aim: Gyrate atrophy of the choroid and retina (GACR) is an extremely rare autosomal recessive inherited disorder characterised by progressive vision loss. To identify the disease-causing gene in a consanguineous Chinese pedigree with GACR, we aimed to accurately diagnose patients with GACR through a combination of next-generation sequencing (NGS) genetic diagnosis, clinical imaging and amino acid metabolic analysis. Methods: A consanguineous Chinese pedigree with GACR, including two patients, was recruited and a comprehensive ophthalmological evaluation was performed. DNA was extracted from a proband and her family members, and the sample from the proband was analysed using targeted NGS. Variants ‎detected by NGS were confirmed by Sanger sequencing and subjected to segregation analysis. Tandem mass spectrometry (MS/MS) was subsequently performed for metabolic assessment. Results: We identified a ‎novel, deleterious, homologous ornithine aminotransferase ( OAT ) variant, c.G248A: p.S83N, which contributes to ‎the progression of GACR in patients. Our results showed that the p.S83N autosomal recessive ‎variant of OAT is most likely ‎pathogenic, with changes in protein stability drastically decreasing functionality. MS/MS verified that ornithine levels in patients were significantly elevated. Conclusions: Recruitment of a third-degree first cousin consanguineous marriage family with GACR allowed us to identify a novel pathogenic OAT variant in the Chinese population, broadening the mutation spectrum. Our findings reported the diagnostic value of a combination of NGS, retinal imaging and metabolic analysis of consanguineous marriage pedigrees in low-income/middle-income and low-incidence countries, including China, and may help to guide accurate diagnosis and ‎treatment of this disease.